Transition 212-303 may help for detection of methylene in a cool cosmic object - Sharma, M. K.; Chandra, S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Methylene is an important astrochemical compound. Though its laboratory spectrum was analyzed in 1982, its first unambiguous detection could be feasible after more than one decade in the hot core of Orion-KL nebula and the approximate molecular cloud of the continuum source W51M through its emission line 404-313. Since then waiting of its further detection has now broken as it has been detected in W51 E, W51 M, W51 N, W49 N, W43, W75 N, DR21, and S140 star forming regions, and in W3 IRS5 through the same transition 404-313. To find potential lines of methylene, we have performed Sobolev LVG analysis of each of the ortho and para species of methylene, considering 10 rotational levels having energy up to 324 cm-1. We have found only three lines, 404-313, 505-414 and 212-303 of methylene, which may help for its detection in a cosmic object. The line 212-303 lying at the lowest energy may be more helpful in a cosmic object having low kinetic temperature. Метилен - важное астрохимическое соединение. Хотя его лабораторный спектр был проанализирован в 1982г., он впервые был достоверно обнаружен через более чем одно десятилетие в горячем ядре туманности Орион-KL и близком молекулярном облаке источника непрерывного излучения W51Mчерез его эмиссионную линию 404-313. С тех пор переход 404-313 был обнаружен в областях звездообразования W51 E, W51 M, W51 N, W49 N, W43, W75 N, DR21 и S140, а также в W3 IRS5. Чтобы найти потенциальные линии метилена, мы провели анализ LVG по Соболеву для каждого из орто- и пара-видов метилена, рассматривая 10 вращательных уровней с энергией до 324 см-1. Мы нашли только три линии, 404-313, 505-414 и 212- 303 метилена, которые могут помочь в его обнаружении в космических объектах. Линия 212-303, лежащая на самом низком энергетическом уровне, может быть более полезной в случае космических объектов, имеющих низкую кинетическую температуру.
Keywords: Astrophysics